The Effect of Changing Arterial Transducer Position on Stroke Volume Measurements Using FloTrac System Version 4.0: A Pilot Experimental Study. (15th June 2021) - Ito, Jiro; Kawakami, Daisuke; Morimoto, Takeshi; Ueta, Hiroshi; Shimozono, Takahiro; Mima, Hiroyuki
Abstract : Supplemental Digital Content is available in the text. Abstract : Objectives: We conducted a pilot study using an experimental study protocol to evaluate the measurement error of arterial pulse contour analysis-derived stroke volume due to improper transducer leveling during the passive leg raising test and the impact of such error on the determination of fluid responsiveness. Design: Prospective observational study. Setting: A medical-surgical ICU at a tertiary referral center in Kobe, Japan. Patients: Consecutive critically ill adult patients using the FloTrac system Version 4.0 (Edwards Lifesciences, Irvine, CA) for hemodynamic monitoring between September 1, 2018, and November 31, 2018. Interventions: None. Measurements and Main Results: Using 20 patients, we estimated the change in the zero-reference level of an arterial transducer during head-down tilting as the vertical distance between the zero-reference levels of the transducer in the 45° semi-recumbent and supine positions. Using the FloTrac system Version 4.0, we recorded the hemodynamic variables every 20 seconds for 180 seconds at each of the following three points: 1) baseline, 2) after the transducer was elevated by the predetermined distance, and 3) after the transducer had returned to baseline. With respect to the predetermined change in the transducer level, a mean value of 18 ± 3 cm resulted in an increase in stroke volume measurement (mean value, 11 mL/beat; 95% CI, 10–13). This value corresponded to 20% (95% CI, 18–23%) of the baseline value 20 seconds after changing the transducer level. A significant correlation was observed between the predetermined change in the transducer level and the increase in the measured stroke volume ( r 2 = 0.58; p < 0.001). CONCLUSIONS: When using the FloTrac system Version 4.0, a rapid increase in stroke volume was observed after elevating the arterial transducer. Clinicians and researchers are advised that proper leveling of the arterial transducer is necessary in order to accurately assess the change in arterial pulse contour analysis-derived stroke volume during the passive leg raising test.